EFFECTIVE ELECTRONIC TUTORIAL - Andrei A. Fedoseev (Открытое образование (Москва), 2016)
The article analyzes effective electronic tutorials creation and application based on the theory of pedagogy. Herewith the issues of necessary electronic tutorial functional, ways of the educational process organization with the use of information and communication technologies and the logistics of electronic educational resources are touched upon.